Politik Hukum terhadap Perlindungan Hukum UMKM Pasca Berlakunya Undang-Undang Nomor 11 Tahun 2020 - Saiful, Saiful; Putra, Anggar (CV. Creative Tugu Pena, 2024)
The presence of the Job Creation Law is the government's form of legal reconstruction of protection for MSMEs, both from the licensing, capital and legal protection aspects. The aim of this research is to find out how the legal politics of protecting MSMEs are in Indonesia after the enactment of the Job Creation Law. The research method, namely library research, is used to collect data from various literature. The nature of the research is analytical descriptive. Normative juridical research approach. Then use primary and secondary data as well as data collection techniques then analyze the data to reach the conclusion stage. The research results show that from the capital aspect, the central government allocates special allocation funds to support funding for regional governments in the context of empowerment and development activities for MSMEs. Meanwhile, from the licensing aspect, the central and regional governments, in accordance with their authority, carry out guidance and registration for MSMEs based on established norms, standards and procedures. Apart from that, registration can be done online and offline by attaching your KTP. Meanwhile, from the aspect of legal aid, the government is identifying legal problems faced by MSMEs, disclosing information regarding legal aid services, allocating budgets for implementing legal aid programs and services. Keywords: Legal Politics, MSMEs, Job Creation Law